Influence of processing temperature on quality attributes of meat analogues fortified with l-cysteine. (April 2023) - Taghian Dinani, Somayeh; Allaire, Noémie; Boom, Remko; van der Goot, Atze Jan
Abstract: Meat analogues, mimicking the textural and sensorial properties of meat, could help consumers transition from animal-based foods to plant-based ones. However, improving the quality attributes of meat analogues, especially their textural properties is crucial to convincing more consumers to include these products in their diet. Here the effect of l -cysteine at a concentration of 0.2% in pea protein isolates (PPI) and wheat gluten (WG) blends was investigated according to the processing temperature (100, 110, 120, 130, 140, and 150 °C) in the high-temperature shear cell (HTSC). The macrostructure of fibers, as well as mechanical, microstructural, and quality attributes of products, were investigated to characterize the influence of l -cysteine on the PPI-WG blends processed at different temperatures. The results of this study showed that l -cysteine had different effects at different processing temperatures. It weakened the product structure and prevented fiber formation at processing temperatures of 100 and 110 °C. This effect was also observed at 140 and 150 °C but to a lesser extent. Conversely, at processing temperatures of 120 and 130 °C, the structure of the products with l -cysteine was stronger than those without l -cysteine, and they presented thicker fibers in visual pictures as well as the pictures obtained by scanning electron microscopy. It is concluded that l -cysteine can improve the textural properties of the meat analogues under precise processing temperatures. Thus, the potential of l -cysteine for improving the textural and quality attributes of meat analogues represents an important step towards the acceptance of a prevailing plant-based diet. Graphical abstract: Image 1 Highlights: l -cysteine (0.2%) at different processing temperatures was tested in meat analogue. It was investigated at 100, 110, 120, 130, 140, and 150 °C in PPI-WG protein blend. l -cysteine can improve meat analogue quality under precise processing temperatures. Meat analogues containing l -cysteine were strong and fibrous at 120 and 130 °C. It weakened product structure and prevented fiber formation at other temperatures.